Truth and Informative Truthfulness. The Spanish model - del Hierro, José Luis (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The terms “truth” and “truthfulness – veracity”, “truthful” and “verified”, are, beyond their doubtless similarities, radically different. In the sphere of information, both in its legal and its ethical dimensions, “truth” and “truthful” have been replaced by the terms “truthfulness” and “verified” as central elements of the right to be informed. Is this replacement coincidental, irrelevant or insignificant? The aim of this article is to demonstrate that by no means this is a minor, incidental or a trivial issue. On the contrary, said mutation responds to very specific reasons which will be examined in the following pages. In order to do so, I will analyze the concepts “truth” and “truthfulness” by briefly tracing back their origins and evolution. Once this is done, I will apply both terms to the sphere of information, firstly in its theoretical dimension, and secondly in its practical implementation, by focusing on the jurisprudence created by the Spanish Constitutional Court and how it has built and given content to the concept of “informative truthfulness”. Finally, this paper will analyze the impact of this phenomenon in different areas.
Keywords: Truth; Truthfulness-Veracity; Informative Truthfulness; Accuracy; Methods to Acquire the Truth; Public Free Communication; Participatory Democracy; Clash of Rights; Weighting; Due Diligence; Transparency